Zigbee Technology in Intelligent Electric Leakage Protection System Applied Research - Deng Lei-lei; Zhang Xian (Institute of Advanced Engineering and Science, 2013)
Aiming at inconvenient wiring and low flexibility of current wired sensor network,An implementation method for real-time monitoring system based on ZigBee wireless network is proposed in this paper. in view of existing selective earth leakage protection device of low sensitivity, poor reliability problems, proposed one kind based on the zero sequence current feature selectionSelective leakage protection and line selection method; analysis of power supply system leakage fault branch of zero-sequence current logical relations, introduced based on the zero sequence current featuresVolume selective leakage protection principle and the realization method of fault line selection.As a Zigbee wireless sensor technology, Its application to the grid. Analyze leakage protection system in relation to the past system of superior performance and favorable conditions, And its features and system design of a simple program to explain the analysis and application of specific measures. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3027